The effect of attentional focus in balancing tasks: A systematic review with meta-analysis - Kim, T.; Jimenez-Diaz, J.; Chen, J. (Journal of Human Sport & Exercise, 2017)
Purpose: The present study was to use the aggregate data meta-analytic approach to examine the effects of attentional focus during balancing tasks in motor learning. Method: A literature search was conducted based on five electronic database searches, cross-referencing and expert review. Studies included randomized trials of external (EF) versus internal focus (IF). Risk of bias was assessed using a self-developed instrument. Random effects models using the standardized mean difference effect size (ES) were used to pooled results. Heterogeneity was examined using the Q statistic and inconsistency using I2. Results: Of 790 studies screened, 16 representing 541 males and females and up to 17 ES met the inclusion criteria. Analyses indicated that the EF groups outperformed the IF groups for acquisition phase (ES= 0.48, n= 16; CI95%= 0.07 to 0.90, Q= 68.7, I2= 78.2%), retention (ES= 0.44, n= 17, CI95%= 0.14 to 0.74; Q= 26.1, I2= 38.6%), and transfer (ES= 1.41, n= 4, CI95%= 1.00 to 1.82, Q= 22, I2= 0%). Conclusion: The overall results suggest that EF results in better balance learning when compared to IF.